Change Management Strategies in Facing Digital Business Challenges and the Development of Artificial Intelligence - Panotogomo, Aam Waro’ (Universitas Negeri Makassar, 2025)
The rapid development of the digital world and advancements in Artificial Intelligence (AI) technology have presented significant challenges for companies globally. To survive and thrive in the digital era, organizations must implement effective change management strategies. This study employs a qualitative approach to explore the change management strategies that can be applied to address the challenges of digital business and the evolution of AI. The research method includes in-depth interviews and case studies of several companies that have successfully implemented change management strategies in the context of digital transformation and AI integration. Data obtained from interviews with company leaders and technology experts were analyzed thematically to identify patterns and best practices in managing changes related to technological developments. The findings suggest that effective strategies include visionary leadership, skills training for employees, and the creation of a collaborative ecosystem between humans and technology. Companies that successfully manage these changes can leverage digital technologies and AI to enhance efficiency, productivity, and competitiveness. Conversely, companies that fail to adapt to these changes risk falling behind in business competition. Therefore, this research emphasizes the importance of inclusive and sustainable change management in facing technological challenges in the business world.